Explanation of the geological map of the country east of Kariba - Broderick, T J (Rhodes University, Faculty of Science, Department of Geology, 1977)
The area covers part of the western end of the Zambezi Metamorphic Belt as it is known in Rhodesia. Most of the rocks are paragneisses of various ages that have suffered a long and complex history which has taken them into the highest facies of metamorphism and into the realm of granitization. Only the Karoo sediments of the Zambezi Valley are unaffected by these metamorphic events. From the scanty geochronological results obtainable from the north of Rhodesia, the history of this area started more than 2 500 million years ago. In the east and south-east of the mapped area are a group of highly migmatized granitic gneisses which represent a continuation westwards of similar rocks found in the area described in Bulletin 51 by Wiles (1961}. These Urungwe Paragneisses are regarded as forrning the basement on which all other rocks in the area lie, although their relationship with the Basement Complex is unknown. Climatically Kariba is hot and humid. Mean summer temperatures average 30°C (86°F), with temperatures in October that often exceed 40°C (100°F). Away from the Lake the humidity decreases and the increased altitudes above the Escarpment have a cooling effect. The township's mean annual rainfall is 665 millimetres (26,2 inches), most of which falls in the months between November and February. Basically. the area is well timbered but population pressures in the tribal areas, and depredation by elephants elsewhere, have made serious inroads upon the natural vegetation. The gneissic terrain above the Escarpment is characterized by mufuti trees (Brachystegia boehmiz). The baobab (Adansonia digitata) is common in the larger river valleys and in the low-lying area surrounding the lake shore where it occurs together with mopane (Colophospermum mopane) and thick jessie bush. In the river valleys, trees typical of the Zambezi Valley are common and include the tamarind (Tamarindus indica), mumvey (Kigelia africana) and Steculia species. Buffalo beans (Mucuma coriacea) are not uncommon in grassy river-beds. Physiographically, the area can be subdivided into three distinct regions, all of which have a marked geological control. They are- (1) The fault-lined Gwembe trough which has subsequently been inundated by the waters of Lake Kariba to an average altitude of 487 metres (1 600 feet) above sea level since the completion of the dam across the upstream entrance to the Kariba Gorge in 1960. The fiat land that now forms part of the lake shore is underlain by sediments of Karoo age and these, in the mapped area, occupy the Charara and Gachegache Basins, that lie to the north and south respectively of the Msango Range. These fiat-lying areas give way sharply to the gneissic terrain of the Zambezi Metamorphic Belt along the fault-lined Zambezi Escarpment. (2) The northern boundary of the area and the Msango Range are underlain by metasediments of the Makuti Group. The relief is strongly influenced by the regional geological structure of these complexly folded rocks with resistant meta-arkose and quartzite forming the sharp ridges and metapelites occupying the valleys. The ridges and valleys trend eastwards in the Msango Range, but along the northern boundary they trend north-westwards. (3) The linear topographic features of the Makuti Group terrain give way southwards to the older gneisses along an abrupt scarp edge, the base of which is marked by the Tsororo River. This terrain of gneisses is very rugged and highly dissected above the Zambezi Escarpment until it flattens out, at about 900 metres (2 950 feet) above sea level, into the Urungwe Tribal Trust Lands. In the rugged country above the Escarpment, granulites of the Piriwiri Group stand out above the gneisses as steep-sided conical bills. The country rises in a series of fault-lined steps to its highest point, at Nyamangwe trigonometrical beacon, which stands at 1 336 metres (4 382 feet) above sea level.
Keywords: Geology -- Kariba, Lake (Zambia and Zimbabwe) -- Maps; Geology -- Kariba, Lake (Zambia and Zimbabwe)